2006
DOI: 10.2353/ajpath.2006.050555
|View full text |Cite
|
Sign up to set email alerts
|

p21Cip1 Is Required for the Development of Monocytes and Their Response to Serum Transfer-induced Arthritis

Abstract: One of the central functions of cyclin-dependent kinase inhibitors, such as p21, p27, or p16, is to prevent entry into the cell cycle. However, the question remains as to whether they have other functions in the cell. We previously demonstrated that overexpression of p21 in fibroblasts isolated from patients with rheumatoid arthritis decreases the production of proinflammatory molecules. Overexpression of p21 has been also shown to reduce the development of experimental arthritis in mice and rats. To explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 54 publications
3
46
0
Order By: Relevance
“…We now additionally show that the hyperproliferative phenotype seen in p21 Cip1-/-mice is associated with an increased number of inflammatory macrophages in the early phase of vascular wound repair. While other researchers have investigated this phenomenon in different settings, our findings are broadly consistent with the fact that p21 Cip1 plays an important role in regulating cell proliferation and monocyte/macrophage differentiation (21,22). However, BM transplantation experiments demonstrated that the enhanced neointimal formation that was observed in p21 -/-mice could not be recapitulated by transplanting p21 -/-BM into p21 +/+ mice.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We now additionally show that the hyperproliferative phenotype seen in p21 Cip1-/-mice is associated with an increased number of inflammatory macrophages in the early phase of vascular wound repair. While other researchers have investigated this phenomenon in different settings, our findings are broadly consistent with the fact that p21 Cip1 plays an important role in regulating cell proliferation and monocyte/macrophage differentiation (21,22). However, BM transplantation experiments demonstrated that the enhanced neointimal formation that was observed in p21 -/-mice could not be recapitulated by transplanting p21 -/-BM into p21 +/+ mice.…”
Section: Discussionsupporting
confidence: 75%
“…p21 Cip1 transcription is activated by p53, and p21 Cip1 is part of a negative feedback mechanism that controls p53 activity during apoptosis (20). p21 Cip1 has been shown to be an important mediator of inflammation, VSMC proliferation (21,22), and vascular proliferative disease (23)(24)(25)(26)(27). Of particular relevance, p21 knockout mice have been shown to exhibit enhanced neointimal formation following arterial injury (28).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the observations that p21-deficient (p212/2) mice are resistant to serum transfer-induced inflammatory arthritis (23), and peritoneal macrophages from p212/2 mice exhibit a higher phagocytotic capacity and lower expression of cytokines such as IL-1b, macrophage inflammatory protein (MIP)-1, and MIP-2 than do their wild-type (WT) counterparts (24). Moreover, genetic knockout of p21 attenuated angiotensin II-induced NF-kB activation by decreasing the production of reactive oxygen species (ROS) in vitro and in vivo (25).…”
supporting
confidence: 71%
“…The severity of myocarditis was judged by percentage area of the myocardium with inflammation as described previously. 24,25 Five fields of view (ϫ100 magnification) of each slide were chosen randomly, and three different sections per mouse were examined. The entire areas of the fields and of regions affected by myocarditis were determined with the use of ImageJ software (NIH) and the percent area of the myocardium undergoing inflammation (affected/entire area in percent) was calculated and averaged.…”
Section: Histopathologymentioning
confidence: 99%